Rheological behavior and structural interpretation of model waxy oils under gelling conditions - Marinho, Thiago Oliveira (2019)
The gelation of waxy crude oils represents a major challenge to safe and economic petroleum production. At temperatures below the Wax Precipitation Temperature (WPT) a fraction of wax molecules precipitates as solid crystals. Under quiescent conditions, the precipitation and wax deposition are enhanced. The crude oil trapped in the pipelines below the WPT may become a waxy-oil gel because of the interlocking of solid wax crystals. This gel cannot be broken with the original steady-state flow operating pressure applied before gelation. Thus, the flow behavior of waxy crude oils under gelling conditions is of crucial importance in the design of pipelines, storage aspects, and for remediation purposes of clogged pipes. In this regard, this Thesis presents a better understanding of the gel-fluid phase transition, based on the rheological behavior of gelled model waxy oils. The investigation encompassed four different commercial waxes solubilized in a mineral oil matrix, molecularly characterized by means of thermal analysis, X-ray scattering techniques, polarized light microscopy, among other procedures. Apparent wall slip, one of the main challenges reported in the rheological characterization of structured materials, is addressed beforehand. The influence of experimental variables on the yield stress of gelled oils and the wax network restructuring level after gel breakage is then evaluated. The relationship among different wax chemical structures and the consecutive yield stress response is also investigated. Scaling models were derived to better understand the microstructure and the wax crystals organization of gelled oils, and also to quantitatively describe their viscoelastic properties. The results presented and discussed in this Thesis incorporate scientific and industrial interest, since they may be useful for flow assurance techniques.